The yeast plasmid: a highly persistent selfish DNA element - Jayaram, Makkuni (Henry Stewart Talks, 2008)
The yeast plasmid as a highly optimized design for a multi-copy selfish DNA element, The need for an active partitioning system for the segregation of a high copy plasmid, Coupling between plasmid segregation and chromosome segregation, Poaching of host factors required for chromosome segregation by the plasmid partitioning system, Cohesin mediated equal segregation of duplicated plasmid clusters